KAT2A Promotes Hepatitis B Virus Transcription and Replication Through Epigenetic Regulation of cccDNA Minichromosome - Qin, Yi-Ping; Yu, Hai-Bo; Yuan, Si-Yu; Yang, Zhen; Ren, Fang; Wang, Qing; Li, Fan; Ren, Ji-Hua; Cheng, Sheng-Tao; Zhou, Yu-Jiao; He, Xin; Zhou, Hong-Zhong; et al. (Frontiers in Microbiology, 2022)
Hepatitis B virus (HBV) infection remains a major health problem worldwide. Sufficient maintenance of the HBV covalently closed circular DNA (cccDNA), which serves as a template for HBV transcription, is responsible for the failure of antiviral therapies. While accumulating evidence suggests that cccDNA transcription is regulated by epigenetic machinery, particularly the acetylation and methylation of cccDNA-bound histone 3 (H3) and histone 4 (H4), the potential contributions of histone succinylation and related host factors remain obscured. Here, by screening a series of succinyltransferases and desuccinylases, we identified KAT2A as an important host factor of HBV transcription and replication. By using HBV-infected cells and mouse models with HBV infection, KAT2A was found to affect the transcriptional activity of cccDNA but did not affect cccDNA production. Mechanism studies showed that KAT2A is mainly located in the nucleus and could bind to cccDNA through interaction with HBV core protein (HBc). Moreover, we confirmed histone H3K79 succinylation (H3K79succ) as a histone modification on cccDNA minichromosome by using the cccDNA ChIP-Seq approach. Importantly, KAT2A silencing specifically reduced the level of cccDNA-bound succinylated H3K79. In conclusion, KAT2A promotes HBV transcription and replication through epigenetic machinery, and our findings may provide new insight into the treatment of HBV infection.